Lack of contribution of nitric oxide synthase to cholinergic vasodilation in murine renal afferent arterioles - Park, Sungmi (Am J Physiol Renal Physiol, 2018)
We have previously reported significant increases in neuronal nitric oxide synthase (NOS) immunostaining in renal arterioles of angiotensin type 1A receptor (AT1A) knockout mice, and in arterioles and macula densa cells of AT1A/AT1B knockout mice. The contribution of nitric oxide derived from endothelial and macula densa cells in the maintenance of afferent arteriolar tone and acetylcholine-induced vasodilation was functionally determined in kidneys of wild-type, AT1A, and AT1A/AT1B knockout mice. Acetylcholine-induced changes in arteriolar diameters of in vitro blood-perfused juxtamedullary nephrons were measured during control conditions, in the presence of the nonspecific NOS inhibitor, N(ω)-nitro-l-arginine methyl ester (NLA), or the highly selective neuronal NOS inhibitor, N(5)-(1-imino-3-butenyl)-l-ornithine (VNIO). Acetylcholine (0.1 mM) produced a significant vasoconstriction in afferent arterioles of AT1A/AT1B mice (−10.9 ± 5.1%) and no changes in afferent arteriolar diameters of AT1A knockout mice. NLA (0.01–1 mM) or VNIO (0.01–1 μM) induced significant dose-dependent vasoconstrictions (−19.8 ± 4.0% 1 mM NLA; −7.8 ± 3.5% 1 μM VNIO) in afferent arterioles of kidneys of wild-type mice. VNIO had no effect on afferent arteriole diameters of AT1A knockout or AT1A/AT1B knockout mice, suggesting nonfunctional neuronal nitric oxide synthase. These data indicate that acetylcholine produces a significant renal afferent arteriole vasodilation independently of nitric oxide synthases in wild-type mice. AT1A receptors are essential for the manifestation of renal afferent arteriole responses to neuronal nitric oxide synthase-mediated nitric oxide release.